Pemberian Lilin Aromaterapi Lavender Terhadap Penurunan Kecemasan Pada Ibu Hamil Trimester III - Failuna Azizah; Septi Tri Aksari; Norif Didik Nur Imanah; Ellyzabeth Sukmawati (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Anxiety is a condition where a person experiences discomfort due to uncertainty about something that will happen.  This becomes an unpleasant and challenging response, unclear thoughts about what will happen in the future.  Non-pharmacological therapy can be done to reduce anxiety by providing lavender aromatherapy.  Lavender is a flower that has a distinctive and soft odor with the main compounds linalyl acetate and linalool which function to reduce anxiety.  It can also restore the mood, making a person relax while inhaling the aroma of lavender.  This study aims to determine the effectiveness of giving lavender aromatherapy candles to reduce anxiety in third trimester pregnant women.  This research is qualitative research with case studies with data sources and data types using primary data obtained from interviews, examinations and observations as well as secondary data obtained from relevant sources.  The implementation technique was carried out by Mrs.  N by giving lavender aromatherapy candles for a duration of approximately 10-15 minutes a day and conducting an evaluation after administration with the results showing that there is an effect of giving lavender aromatherapy candles in reducing anxiety about facing childbirth